Geographical distribution and pathogenesis of ticks and tick-borne viral diseases - Shah, Taif; Li, Qian; Wang, Binghui; Baloch, Zulqarnain; Xia, Xueshan (Frontiers in Microbiology, 2023)
Ticks are obligatory hematophagous arthropods that harbor and transmit infectious pathogens to humans and animals. Tick species belonging to Amblyomma, Ixodes, Dermacentor, and Hyalomma genera may transmit certain viruses such as Bourbon virus (BRBV), Dhori virus (DHOV), Powassan virus (POWV), Omsk hemorrhagic fever virus (OHFV), Colorado tick fever virus (CTFV), Crimean-Congo hemorrhagic fever virus (CCHFV), Heartland virus (HRTV), Kyasanur forest disease virus (KFDV), etc. that affect humans and certain wildlife. The tick vectors may become infected through feeding on viraemic hosts before transmitting the pathogen to humans and animals. Therefore, it is vital to understand the eco-epidemiology of tick-borne viruses and their pathogenesis to optimize preventive measures. Thus this review summarizes knowledge on some medically important ticks and tick-borne viruses, including BRBV, POWV, OHFV, CTFV, CCHFV, HRTV, and KFDV. Further, we discuss these viruses' epidemiology, pathogenesis, and disease manifestations during infection.